2017
DOI: 10.1097/eja.0000000000000641
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium sulphate improves pulmonary function after video-assisted thoracoscopic surgery

Abstract: cris.nih.go.kr identifier: KCT0001410.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…In a clinical trial with a total of 2907 randomized patients, atomized magnesium sulfate, combined with inhaled β2-agonist and ipratropium bromide, have modest additional benefits in terms of pulmonary function and hospitalization ( Knightly et al, 2017 ). Additionally, intraoperative administration of magnesium sulfate (50 mg/kg intravenously for 10 min, followed by continuous infusion of 15 mg/kg/h during the operation) improves lung function in patients receiving video-assisted thoracoscopic surgery, and reduces the doses of rocuronium and postoperative analgesics ( Sohn et al, 2017 ).…”
Section: Prevention and Treatment Of Magnesium For Lung Symptoms And mentioning
confidence: 99%
“…In a clinical trial with a total of 2907 randomized patients, atomized magnesium sulfate, combined with inhaled β2-agonist and ipratropium bromide, have modest additional benefits in terms of pulmonary function and hospitalization ( Knightly et al, 2017 ). Additionally, intraoperative administration of magnesium sulfate (50 mg/kg intravenously for 10 min, followed by continuous infusion of 15 mg/kg/h during the operation) improves lung function in patients receiving video-assisted thoracoscopic surgery, and reduces the doses of rocuronium and postoperative analgesics ( Sohn et al, 2017 ).…”
Section: Prevention and Treatment Of Magnesium For Lung Symptoms And mentioning
confidence: 99%
“…22,47,49 There was a reduction in extubation time after dexmedetomidine 22 Residual neuromuscular block. Two studies 26,47 reported data on train-of-four ratio on arrival to PACU. For magnesium, the TOF ratio after was greater than 0.9 for both intervention and normal saline, 26 whereas lidocaine was associated with a higher TOF ratio.…”
Section: Alpha2-adrenergic Agonistsmentioning
confidence: 99%
“…Two studies 26,47 reported data on train-of-four ratio on arrival to PACU. For magnesium, the TOF ratio after was greater than 0.9 for both intervention and normal saline, 26 whereas lidocaine was associated with a higher TOF ratio. 47 No other studies reported either clinical or electromyographic data regarding residual neuromuscular block.…”
Section: Alpha2-adrenergic Agonistsmentioning
confidence: 99%
“…A total of 1,952 patients over the age of 19 years were diagnosed with NSCLC and underwent VATS lobectomy between January 1, 2011, and July 31, 2017. Among these patients, the following cases were excluded from the analysis: 1) 86 cases with missing data on pain outcomes or on TSC; 2) 92 cases with intraoperative conversion of the procedure to open thoracotomy, bilobectomy, or pneumonectomy; 3) 38 cases of surgery involving organs outside the thoracic cavity; 4) 12 cases in which epidural analgesia was performed; and 5) 4 patients who participated in clinical trials using intraoperative magnesium sulfate infusion [12]. Thus, a total of 1,720 patients were included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we included patients who underwent sublobar resection on other ipsilateral pulmonary lobes in the ‘lobectomy’ category but excluded those who underwent sublobar resection on the lung contralateral to the one on which lobectomy had been performed. The exclusion criteria included the following: requirement for additional operations within two days after lobectomy; intraoperative conversion of the procedure to open thoracotomy; conversion of the procedure to bilobectomy or pneumonectomy; missing or inaccurate data on pain outcomes or TSC; requirement for thoracic epidural analgesia; patients who participated in randomized trials that required the intraoperative infusion of magnesium sulfate [12]; and surgery involving organs outside the thoracic cavity.…”
Section: Methodsmentioning
confidence: 99%